Industry Professionals’ Views on How to Create Brand Equity for Medical Marijuana Brands - Brown, Hayley (The IIE, 2019)
It is no longer illegal to privately cultivate and/or use marijuana for recreational and/or medical purposes in South Africa. However, many South Africans still attach a stigma to marijuana regardless of its purpose. This acts as a barrier for medicinal brands operating within this industry, to be successful. However, research shows that brand equity is a crucial factor contributing to the success of a brand. It is therefore important to find ways in which brand equity can be created for medical marijuana brands to overcome the stigma that many South Africans attach to marijuana use. This study researched ways in which brand equity could be created for medical marijuana brands operating within KwaZulu- Natal, South Africa. Qualitative research was conducted using interviews, interview schedules and ethnography as data-collection methods. This allowed the researcher to obtain in-depth, insightful responses from marketing and/or marijuana Industry Professionals. As a result of this research, it was identified that brand awareness, brand loyalty, brand image and perceived quality (all brand equity components) contribute to the success of a brand. It is therefore highly advisable for medical marijuana brands to focus on these components in order to build brand equity to overcome the stigma attached to marijuana.
Keywords: Brand; Brand equity; Medicinal brand; Brand awareness